1987
DOI: 10.1111/j.1365-2125.1987.tb03140.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a new hypnotic imidazo‐pyridine (zolpidem) as oral premedication.

Abstract: 1 A new imidazo‐pyridine hypnotic (zolpidem 10 mg and 20 mg) was compared with placebo as premedication before general anaesthesia in female patients undergoing minor gynaecological surgery. Efficacy and tolerance before and after anaesthesia were assessed. Psychomotor testing was used to study recovery from anaesthesia. 2 Both doses of zolpidem produced good sedation pre‐operatively but only the higher dose was associated with anterograde amnesia. 3 Premorbid anxiety scores were low in the group of patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
1
7
1
1
Order By: Relevance
“…13 Additionally, one study has demonstrated utility of zolpidem as oral premedication in adults prior to general anesthesia. 14 Blumer et al 15 reported no serious adverse events in a controlled trial of zolpidem in the treatment of insomnia in children with attention-deficit/hyperactivity disorder in children. Our hypothesis was that the medication profile of zolpidem makes it a promising premedication for use in children since a sleepy or sleeping child may not respond to anxiety triggers.…”
Section: Some Children Verbalize Their Fears While Others Show Behavimentioning
confidence: 99%
See 1 more Smart Citation
“…13 Additionally, one study has demonstrated utility of zolpidem as oral premedication in adults prior to general anesthesia. 14 Blumer et al 15 reported no serious adverse events in a controlled trial of zolpidem in the treatment of insomnia in children with attention-deficit/hyperactivity disorder in children. Our hypothesis was that the medication profile of zolpidem makes it a promising premedication for use in children since a sleepy or sleeping child may not respond to anxiety triggers.…”
Section: Some Children Verbalize Their Fears While Others Show Behavimentioning
confidence: 99%
“…It has a very rapid onset of action, can be orally administered, and is rapidly metabolized and eliminated . Additionally, one study has demonstrated utility of zolpidem as oral premedication in adults prior to general anesthesia . Blumer et al reported no serious adverse events in a controlled trial of zolpidem in the treatment of insomnia in children with attention‐deficit/hyperactivity disorder in children.…”
Section: Introductionmentioning
confidence: 99%
“…A high proportion of the hemodynamic effects of diazepam were attributed to modulation of central pathways and may be due in part to contribution of these tonic receptors. Zolpidem in contrast had no significant effect on blood pressure in humans (Cashman et al, 1987) or in rats (Mailliet et al, 2001). Others report conflicting changes in RR intervals, depending on the dose of zolpidem administered but mainly due to a change in cardiac vagal tone, rather than on sympathetic outflow (Chen et al, 2005).…”
Section: Functional Significance Of Tonic Gabaergic Inhibitionmentioning
confidence: 99%
“…In fact the idea that this tonic inhibition could contribute to overall blood pressure changes is supported by our understanding of the haemodynamic effects in humans of the two modulators used here. Diazepam, which enhances tonic inhibition, causes hypotension and reduces muscle sympathetic activity (Kitajima et al, 2004) while zolpidem, which was without effect on tonic inhibition, does not cause changes in blood pressure in humans (Cashman et al, 1987). Tonic inhibition may also play a role in limiting the frequency of oscillatory activity in other brain regions such as hippocampus (Mann & Mody, 2010), and a component of the effect of bicuculline of rhythmic network activity in the spinal cord slice may due to in part to blockade of the tonic current (Pierce et al, 2010).…”
Section: Gabaergic Interneurones and Influences On Sympathetic Controlmentioning
confidence: 99%